Effect of fertility levels on yield attributes, yieldand quality of Indian mustard (Brassica juncea L.) in irrigated conditions South-Eastern Rajasthan - B.S. Meena; S.N. Meena; Roshan Kumawat; Gajendra Nagar; Adarsh Sharma (Annals of Agricultural Research, 2022)
A field experiment was conducted during rabi season of 2017-18, 2018-19 and 2019-20 at Agricultural Research Station, Kota to study the effect of different fertility levels on growth, yield attributes, yield and quality of Indian mustard (Brassica juncea L.) grown on Vertisol after harvest of urdbean in irrigated condition. The treatment consisted of three levels of nitrogen (80,100 and 120 kg/ha) and two levels of phosphorus (40 and 50 kg/ha) in main plots and three levels of potassium viz. (15, 30 and 45 kg/ha) in sub plots, which were laid out in split-plot design with 3 replication. The application of 100 kg N/ha produced significantly higher seed yield (2738 kg/ha), plant height (219cm), dry matter accumulation/plant (59.3 g), branches/plant (14.4), siliquae/plant (197), seeds/siliqua (15.4), 1000-seed weight (5.0 g), oil content (39.3 %), protein content (21.3 %), net return (`91929/ha) and benefit: cost ratio (3.35) and total nutrient (NPK) uptake by crop (109.7,27.2 and 165.8 kg/ha, respectively) over application of 80 kg N/ha and remained at par with 120 kg N/ha. Similarly, seed yield (2801 kg/ha), dry matter accumulation/plant (62.6 g), branches/plant (14.3), siliquae/plant (200.1), seeds/siliqua (15.4), 1000-seed weight (5.1 g), oil content (39.1 %), protein content (21.3 %), net return (`93984/ha) and benefit: cost ratio (3.39) increased significantly with 50 kg P2 O5 /ha over 40 kg P2 O5 /ha. Whereas, potassium fertilization at 30 kg/ha significantly increased seed yield (2729 kg/ha), plant height (214cm), dry matter accumulation/plant (58.4 g), branches/plant (14), siliquae/plant (192.7), seeds/ siliqua (15.5), 1000-seed weight (5.1 g), oil content (39.0 %), protein content (21.2 %), net return (91161/ha) and benefit: cost ratio (3.32) over 15 kg K2 O/ha and remained at par with 45 kg K2 O/ha. The available nutrients in soil and total nutrient uptake by crop followed the similar trend as recorded in yield attributes and seed yield in phosphorus and potassium fertilizers treatments. The highest positive net gain of NPK over initial status was also noted under the nutrient levels of 120:50:45 kg NP2 O5 K2 O/ha. Thus, it was concluded that mustards sown after the harvested of urdbean fertilized with 100:50:30 kg NP2 O5 K2 O/ha was found effective for getting high seed yield and net returns in irrigated conditions of south- eastern Rajasthan.